West Nile virus emergence in humans in Extremadura, Spain 2020 - Macias, Alicia; Martín, Paloma; Pérez-Olmeda, Mayte; Fernández-Martínez, Beatriz; Gómez-Barroso, Diana; Fernández, Esperanza; Ramos, Julian Mauro; Herrero, Laura; Rodríguez, Saray; Delgado, Elena; Sánchez-Seco, Maria Paz; Galán, Miguel; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The largest human West Nile virus (WNV) frequency of cases in Spain was reported in 2020, being the second most important in Europe that season. Extremadura (southwestern Spain), the region where the first autochthonous human case in Spain in 2004 was retrospectively described, was one of the affected areas, with six human cases. In this work, we described the first WNV human outbreak registered in Extremadura in 2020, focused on the most important clinical aspects, diagnostic results and the control actions followed in this outbreak. From September to October, human WNV infections were diagnosed by molecular and serological methods (an in-house specific qRT-PCR and a commercial ELISA anti-WNV IgM and IgG antibodies) analysing several samples (serum, urine and/or cerebrospinal fluid). Positive serum samples were further tested by serological methods against Usutu and Tick-borne encephalitis viruses to analyzed cross-reactions using commercial kits and these results were confirmed by neutralization assays. In total, six cases of WNV infection (five with neuroinvasive disease and one with fever) were identified. Clinical presentation and laboratory findings are described. No RNA viral was detected in any of the analyzed samples and serological cross-reactivity was detected against the other tested flaviviruses. The largest number of human cases of WNV infection ever registered in Extremadura, Spain, occurred in 2020 in areas were WNV circulation had been reported previously, suggesting to be an endemic area. It is necessary to enhance surveillance for the early detection and implementation of response measures. Molecular and serological methods for WNV diagnosis in several samples are recommended.